Design and Build Android-Based English Learning Media on Descriptive Text Material - Sri Handayani; Fera Ayu Martiyani; Alfonsa Maria Sofia Hapsari; Yudhistiro Pandu Widhoyoko (Formosa Journal of Computer and Information Science, 2022)
This study aimed 1) to find out how to design Android -based English learning media on descriptive text material, 2) to determine the feasibility of Android -based English learning media on descriptive text material at MTS N 2 Surakarta. This study used research and development (R & D) research methods with the research procedure model proposed by Dick and Carey and the ADDIE model consisting of Analysis, Design, Development, Implementation, and Evaluation. Data collection techniques were through interviews, questionnaires, and documentation. Feasibility validation was carried out by media experts, material experts, and English teachers from MTs N 2 Surakarta. Data analysis was using a Likert scale to determine the percentage score of the media feasibility and passes black box testing. The results of this study were 1) to produce an Android -based English learning media on descriptive text material. From the results of the black box testing carried out, the learning media could be operated properly on Android smartphones according to their needs and functions, 2) the feasibility of Android . based English learning media on descriptive text material according to the assessment of media experts was to get a feasibility percentage of 76% with a feasible category, assessment from material experts was to get a feasibility percentage of 82% with a very decent category, and the feasibility assessment by ant English teacher at MTs N 2 Surakarta was to get a feasibility percentage of 80% with a decent category.